Intrageneric Karyotypic Variation in Pseudopaludicola (Anura: Leiuperidae) and Its Taxonomic Relatedness - Favero, Eduardo R.; Veiga-Menoncello, Ana C. P.; Rossa-Feres, Denise C. [UNESP]; Struessmann, Christine; Giaretta, Ariovaldo A.; Andrade, Gilda V.; Colombo, Patrick; Recco-Pimentel, Shirlei M. (Acad Sinica Inst Zoology, 2011)
Eduardo R. Favero, Ana C. P. Veiga-Menoncello, Denise C. Rossa-Feres, Christine Strussmann, Ariovaldo A. Giaretta, Gilda V. Andrade, Patrick Colombo, and Shirlei M. Recco-Pimentel (2011) Intrageneric karyotypic variation in Pseudopaludicola (Anura: Leiuperidae) and its taxonomic relatedness. Zoological Studies 50(6): 826-836. Herein, we report karyological data for Pseudopaludicola frogs, with the main objective to investigate the confusing taxonomic identification of these anurans. The samples analyzed included topotypes of P. falcipes and P. ameghini (currently considered a synonym of P. mystacalis) in addition to specimens of P. mystacalis and P. ternetzi and of 8 additional populations of Pseudopaludicola from several regions of Brazil. Interspecific variations in the chromosome number, location of the nucleolar organizer region (NOR), and banding patterns were observed. The karyotype of P. falcipes consisted of 2n = 22 chromosomes, whereas P. ameghini (sensu Cope 1887) and P. ternetzi had 2n = 20 and P. mystacalis had 2n = 16 chromosomes. The chromosome number 2n = 16 was also found in specimens of populations from Santa Fe do Sul, Vitoria Brazil, Icem, Palestina (southeastern Brazil), Barreirinhas, Urbano Santos (northeastern Brazil), Pocone, and Santa Terezinha (west-central Brazil). Nevertheless, in some individuals from Icem and Pocone, we found 2n = 20 and 2n = 22 chromosomes, respectively. This variation in chromosome number indicates diverse taxa coexisting in sympatry. The karyotypic patterns of 2n = 20 in P. ameghini (sensu Cope 1887) and 2n = 16 in P. mystacalis are clearly indicative of 2 distinct taxonomic units. Therefore, our data corroborate the removal of P. ameghini from synonymy with P. mystacalis as previously suggested. We define the karyotype of P. falcipes as 2n = 22 and of P. ternetzi as 2n = 20 and reinforce the need for a taxonomic revision of this genus. http://zoolstud.sinica.edu.tw/Journals/50.6/826.pdf
Keywords: Pseudopaludicola; Cytotaxonomy; Karyotype; Ag-NOR; C-band